Implemetasi Kebijakan Program bantuan Hukum Bagi Masyarakat Tidak Mampu di Pos Bantuan Hukum YLBHK-DKI Kota Tanjungpinang - Saputri, Pratiwi Reka; Sari, Cica Afrita; Rezeki, Selpi Putri (CV. Publikasi Indonesia, 2022)
Legal assistance is needed for the people of Tanjung Pinang City because of the increasing legal problems that occur in the environment of the poor and legally blind in obtaining legal assistance by providing legal assistance for free. In an effort to realize the values of Pancasila and to realize justice for the unable to get a common position before the law, based on this, the author is interested in conducting research, namely